Living (dangerously) without a fiscal union - Mody, Ashoka (Brussels, 2015)
"The euro area’s political contract requires member nations to rely principally on their own resources when confronted with severe economic distress. Since monetary policy is the same for all, national fiscal austerity is the default response to counter national fiscal stress. Moreover, the monetary policy was itself stodgy in countering the crisis, and banking-sector problems were allowed to fester. And it was considered inappropriate to impose losses on private sector creditors.